Influence of two anti-tumor drugs, pazopanib, and axitinib, on the development and thyroid-axis of zebrafish (Danio rerio) embryos/larvae - Yang, Liu; Tu, Ping-hui; Zhang, Cao-xu; Xie, Rong-rong; Dong, Mei; Jing, Yu; Chen, Xia; Wei, Gang; Song, Huai-dong (Frontiers in Endocrinology, 2023)
Introduction In recent years, the potential toxicities of different pharmaceuticals toward the thyroid system have received increasing attention. In this study, we aim to evaluate the toxic effects of pazopanib and axitinib, two anti-tumor drugs with widespread clinical use, on thyroid function in the zebrafish model. Methods We measured levels of thyroid-related hormones using the commercial Enzyme-Linked Immunosorbent Assay (ELISA) kit. Whole-mount in situ hybridization (WISH) analysis was employed to detect target gene expression changes. Morphology of the thyroid were evaluated by using transgenic Tg (tg: EGFP) fish line under a confocal microscope. The relative mRNA expression of key genes was verified through quantitative real-time polymerase chain reaction (RT‒qPCR). The size and number of the follicles was quantified whereby Hematoxylin–Eosin (H & E) staining under a light microscope. Results The results revealed that fertilized zebrafish embryos were incubated in pazopanib or axitinib for 96 hours, development and survival were significantly affected, which was accompanied by significant disturbances in thyroid endocrine system (e.g., increased thyroid-stimulating hormone (TSH) content and decreased triiodothyronine (T3) and thyroxine (T4) content, as well as transcription changes of genes associated with the hypothalamus-pituitary-thyroid (HPT) axis. Moreover, based on whole-mount in situ hybridization staining of tg and histopathological examination of zebrafish embryos treated with pazopanib and axitinib, we observed a significantly abnormal development of thyroid follicles in the Tg (tg: EGFP) zebrafish transgenic line. Conclusion Collectively, these findings indicate that pazopanib and axitinib may have toxic effects on thyroid development and function, at least partially, by influencing the regulation of the HPT axis. Thus, we believe that the potential thyroid toxicities of pazopanib and axitinib in their clinical applications should receive greater attention.